Customizing Photoredox Properties of PXX‐based Dyes through Energy Level Rigid Shifts of Frontier Molecular Orbitals. Issue 17 (27th February 2018) - Sciutto, Andrea; Fermi, Andrea; Folli, Andrea; Battisti, Tommaso; Beames, Joseph M.; Murphy, Damien M.; Bonifazi, Davide
Abstract: Here we describe the synthesis of electron‐richPXX derivatives in which the energy levels of the excited states have been rigidly shifted through the insertion of imide groups. This has allowed the development of a new series of oxygen‐doped photoredox‐active chromophores with improved oxidizing and reducing properties. Capitalizing on the dehalogenation of organic halides as a model reaction, we could investigate the photooxidative and photoreductive potential of these molecules in model chemical transformations. Depending on the substrate, solvent and dye the reaction mechanism can follow different paths. This prompted us to consider the first chemoselective transformation protocol, in which two different C−Br bonds could be chemoselectively reacted through the sequential photoactivation of two different colorants. Abstract : Look on the bright side : the energy levels of the excited states of a new series of peri ‐xanthenoxanthenes derivatives have been rigidly shifted through the insertion of imide groups. This has allowed detailed investigations on the photoredox properties of these chromophores, demonstrating their ability in promoting light‐activated dehalogenations.